Laparoscopic Excision of Splenic Artery Aneurysm - Kim, Youngjin (Society of Laparoendoscopic Surgeons, 2013)
INTRODUCTION: Splenic artery aneurysm is more frequently diagnosed today with the advancement and liberal use of imaging modalities. A symptomatic aneurysm, an aneurysm of any diameter in a pregnant woman or a woman of childbearing age, and an aneurysm >2 cm are all strong indications for surgery because of a significantly increased risk for splenic artery rupture. CASE DESCRIPTION: A 35-year-old, morbidly obese, African American woman presented with constant left flank pain for 4 weeks. Angiography confirmed a 2.5-cm splenic artery aneurysm near the splenic hilum. Because angioembolization was unlikely to succeed because of extensive collaterals and the aneurysm's proximity to the splenic hilum, laparoscopic excision of the aneurysm with splenectomy was performed. DISCUSSION: We report the successful laparoscopic surgical treatment of a 2.5-cm splenic artery aneurysm. Any splenic artery aneurysm with a significantly increased risk of rupture requires a prompt intervention. Although percutaneous embolization of the splenic artery is the most frequently applied therapy today, surgical repair is preferred for all symptomatic aneurysms because of the greater likelihood of success.